2015
DOI: 10.1039/c5cp04867b
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective on the process of intrinsic point defects in α-Al2O3

Abstract: First-principles plane-wave pseudopotential calculations have been performed to study the charge states and energetics of intrinsic point defects as vacancies, interstitials and antisite atoms in α-Al2O3, and thus a new perspective on the process of intrinsic point defects has been proposed. Considering the various charge states for each intrinsic point defects, V(Al)(3-), V(O)(0), Al(i)(3+), O(i)(2-), Al(O)(3+), and O(Al)(3-), not all in their fully ionized states are found to be most stable and in pure Al2O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 35 publications
2
25
1
Order By: Relevance
“…Multiple authors have studied charged and clustered defects in Al 2 O 3 . 25,[36][37][38][39] They showed that different geometric arrangements and supercell size result in little difference in energy and that the impurity atoms prefer to be clustered due to the binding energy. 25,[36][37][38][39] Using this methodology, supercells were generated in the present work with Mg and/or Si clustered, i.e.…”
Section: Tobias Fruehmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple authors have studied charged and clustered defects in Al 2 O 3 . 25,[36][37][38][39] They showed that different geometric arrangements and supercell size result in little difference in energy and that the impurity atoms prefer to be clustered due to the binding energy. 25,[36][37][38][39] Using this methodology, supercells were generated in the present work with Mg and/or Si clustered, i.e.…”
Section: Tobias Fruehmentioning
confidence: 99%
“…25,[36][37][38][39] They showed that different geometric arrangements and supercell size result in little difference in energy and that the impurity atoms prefer to be clustered due to the binding energy. 25,[36][37][38][39] Using this methodology, supercells were generated in the present work with Mg and/or Si clustered, i.e. the Mg-cluster having 2 Mg atoms substituted for 2 Al atoms and an oxygen vacancy as nearest neighbors, the Si-cluster having 3 Si atoms substituted for 3 Al atoms and an Al vacancy, and the Mg+Si-cluster having 1 Mg and 1 Si substituted for 2 Al atoms.…”
Section: Tobias Fruehmentioning
confidence: 99%
“…The charge states and formation energies of vacancies, interstitial and antisite atoms in pure α-Al 2 O 3 were studied in [13]. It was found that under O-rich and O-deficient conditions the most stable defect is the Al vacancy V 3− Al .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The lattice relaxation, energetics, and electronic structures of different defects can be investigated by this method, which yields important insight into the scientific and technologic interests. For instance, Xiang et al performed first-principles calculations to study the energetics and the charge states of intrinsic point defects in α-Al 2 O 3 , finding that the antisite O Al would be readily formed in in the oxygen rich environment, and a new perspective thus has been proposed on the process of α-Al 2 O 3 defects.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Xiang et al performed first-principles calculations to study the energetics and the charge states of intrinsic point defects in α-Al 2 O 3 , finding that the antisite O Al would be readily formed in in the oxygen rich environment, and a new perspective thus has been proposed on the process of α-Al 2 O 3 defects. 13 Zhao et al conducted the first principles calculations to investigate the intrinsic defects in the wurtzite phase of ZnO, indicating that oxygen vacancy may be the reason for the visible photoluminescence band between 2.3 and 2.5 eV observed in the experiments. 16 However, very limited number of theoretical investigations been reported on the intrinsic defects in VO 2 (M) have, which may be ascribe to the extreme sensitivity of its properties to theoretical approximations.…”
Section: Introductionmentioning
confidence: 99%